O impacto da terceirização sobre os custos de mão-de-obra nas organizações - um estudo de caso em uma empresa de telecomunicações - Garcia, Roberto Bertoldo (2006)
The cost with staff is significant for the organizations in general, a time that Brazil is placed in the top of the countries with bigger expenditures with incubencies in the act of contract. This dissertation describes as the outsourcing process occurs aiming at mainly to the reduction of the man power costs. Outsourcing is an administrative tool, through which, activities that were carried through internally had passed to be carried through by third. Currently this strategy comes being very used in the enterprise ways of the whole world with intention to search advantages, however, the risks is gifts, being able to generate greaters responsibilities. Using of a study of case of a company of telecommunications and the Inter-relations with its partners, either independent work, companies of outsourcing and cooperatives of work, an evolution is verified each more increasing time of practical of outsourcing in all the its forms, that had mainly provided to a reduction of the number of staff of the contracting company and reduction with the man power costs. On the other hand, it is verified that the practical one of the outsourcing finishes being a way to corrupt the rights and to disrespect the Brazilian labor law.